A COMPARATIVE ANALYSIS OF EMOTIONAL INTELLIGENCE AMONG HIGHER SECONDARY STUDENTS - Datta, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The present study attempted to compare the Emotional Intelligence of urban and rural Higher Secondary students. Descriptive Survey research method was used to collect data from 540 Higher Secondary students randomly selected from different undergraduate colleges of Kolkata and its suburbs using the Mangal Emotional Intelligence Inventory (2011). The results of the study showed no significant difference between urban and rural students. The findings indicate that habitat does not significantly influence Emotional Intelligence. The study suggests that environmental and socio-cultural exposure in urban settings may play a facilitating role in enhancing Emotional Intelligence. The study highlights the importance of nurturing Emotional Intelligence among the students through educational and parental practices to promote academic achievement and interpersonal development, psychological and societal well-being.